2018
DOI: 10.3390/cells7090136
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Cell Mechanics by Actin Cytoskeletal Changes Correlate with Strain-Specific Rubella Virus Phenotypes for Cell Migration and Induction of Apoptosis

Abstract: The cellular cytoskeleton is central for key cellular functions, and as such is a marker for diseased and infected cell states. Here we analyzed infection with rubella virus (RV) strains with respect to phenotypes in cellular mechanical properties, cell movement, and viral cytopathogenicity. Real-time deformability cytometry (RT-DC), as a high-throughput platform for the assessment of cell mechanics, revealed a correlation of an increase in cortical filamentous-actin (F-actin) with a higher cellular stiffness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…However, a significant decrease in stiffness is correlated with metastatic potential, with one study having found a 73% reduction in stiffness following metastasis ( Cross et al, 2007 ; Guck et al, 2005 ; Hou et al, 2009 ). Viral infection also induces cortical actin restructuring, with one strain of rubella virus accounting for an increase of 17.8% in Young's modulus, a measure of substrate stiffness ( Kräter et al, 2018 ). Thus, stiffening or softening of cells within tissues may be indicative of transformation.…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant decrease in stiffness is correlated with metastatic potential, with one study having found a 73% reduction in stiffness following metastasis ( Cross et al, 2007 ; Guck et al, 2005 ; Hou et al, 2009 ). Viral infection also induces cortical actin restructuring, with one strain of rubella virus accounting for an increase of 17.8% in Young's modulus, a measure of substrate stiffness ( Kräter et al, 2018 ). Thus, stiffening or softening of cells within tissues may be indicative of transformation.…”
Section: Introductionmentioning
confidence: 99%
“…While viruses are obligate intracellular parasites that have a life cycle requiring the engagements and modification of cytoskeleton at all stages, from invasion through replication to budding and transmission. By far, lots of viruses have been reported that evolved to engage and subvert the cytoskeleton proteins' function, such as RSV (Shahriari et al, 2016 ), Dengue Virus (Wang et al, 2010 ), Rubella virus (Krater et al, 2018 ), avian influenza viruses (Guo et al, 2018 ), rabies virus (Monroy-Gomez et al, 2018 ), Rhinovirus (Michi and Proud, 2018 ). In the present study, the microtubule-associated proteins Tubb5, Tuba3, the intermediate filament proteins Prph, Vim, and microfilament-associated protein Capza1 were down-regulated by echovirus infection, while microfilament-associated protein Actb and keratin-associated protein Krt83 were up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…In each experiment 3 region of interest (ROI) was selected for quantification analysis (Figure 1 B) . Euclidean distance [74] or displacement [75,76] was defined as the linear shortest distance between start and end point of a single cell trajectory (Figure 1 A-iv).…”
Section: On-chip Cell Migration Analysis and Quantificationmentioning
confidence: 99%